Edukasi deteksi dini kanker payudara sebagai upaya pencegahan penyakit kronis mematikan di Kelurahan Kalisegoro Semarang - Eden, Willy Tirza; Savitri, Annisa Aulia; Ni`ma, Neli Syahida; Rahmaniar, Ranita; Alighiri, Dante (INDRA: Jurnal Pengabdian kepada Masyarakat, 2025)
A major health concern for women is breast cancer, which is the most common cause of death in this population and delayed diagnosis is a major contributor to this. This delay often arises from a lack of public understanding about breast cancer and its potential for harm. However, performing regular breast self-exams (BSE) offers a method for early identification. Therefore, this community service aims to socialize the BSE method to The Family Welfare Program (PKK) mothers in Kalisegoro Urban Village. The method used in this socialization process uses direct counseling. This education seeks to increase knowledge and promote the regular use of the BSE method. This community service is descriptive community service and gathering the data through an evaluation questionnaire administered after the activity's completion. A number of respondents in this community service were residents of Kalisegoro Urban Village. These results show that the service team effectively communicated information about the early detection of breast cancer, and the participants responded positively to it.